Memahami Substitusi Penal Dalam Roma 8:1 Melalui Perspektif Teologi Kovenan - Purwougroho, Daniel Pesah (EULOGIA: Jurnal Teologi dan Pendidikan Kristiani, 2025)
Abstract: This paper aims to understand penal substitution in Romans 8:1 through the perspective of covenant theology. Penal substitution is a doctrine that states that Jesus Christ takes the place of man to bear the sins that should have been borne by mankind. Romans 8:1 is the culmination of Paul's argument on justification and forgiveness of sins that can explain penal substitution. The role of Jesus Christ is significant from a covenantal perspective. Through the perfect obedience of Jesus Christ, the covenant of works that could not be fulfilled by man could be fulfilled in Jesus Christ. The obedience of Jesus Christ on the cross also brings believers to experience God's grace and can live in peace with God. Through a descriptive qualitative approach, the author tries to understand penal substitution in Romans 8:1 through a covenantal perspective. The author asserts that Romans 8:1 helps to understand penal substitution from a covenantal perspective because it all boils down to the redemptive work of Jesus Christ. This paper offers an integrative presentation to place Romans 8:1 as the climactic affirmation of penal substitution within the framework of covenant theology.Keywords: Romans 8:1, Penal Substitution, Covenant TheologyAbstrak:Tulisan ini bertujuan untuk memahami substitusi penal dalam Roma 8:1 melalui perspektif teologi kovenan. Substitusi penal merupakan doktrin yang menyatakan bahwa Yesus Kristus menggantikan manusia untuk menanggung dosa yang semestinya ditanggung umat manusia. Roma 8:1 merupakan puncak argumen Paulus mengenai pembenaran dan pengampunan dosa yang dapat menjelaskan substitusi penal. Peran Yesus Kristus sangat signifikan di dalam perspektif kovenan. Melalui ketaatan Yesus Kristus yang sempurna, kovenan kerja yang tidak dapat digenapi oleh manusia dapat terpenuhi di dalam Yesus Kristus. Ketaatan Yesus Kristus di atas kayu salib juga membawa orang percaya mengalami anugerah Allah dan dapat hidup dalam damai sejahtera dengan Allah. Melalui pendekatan kualitatif deskriptif, penulis mencoba memahami substitusi penal dalam Roma 8:1 melalui perspektif kovenan. Penulis menegaskan bahwa Roma 8:1 membantu memahami substitusi penal dalam perspektif kovenan karena semua bermuara kepada karya penebusan Yesus Kristus. Tulisan ini menawarkan penyajian yang integratif utnuk menempatkan Roma 8:1 sebagai penegasan klimaks substitusi penal dalam kerangka teologi kovenan.Kata Kunci : Roma 8:1, Substitusi Penal, Teologi Kovenan